REPRESENTASI INDONESIA DALAM NOVEL TRILOGI TERJEMAHAN KAYA TUJUH TURUNAN KARYA KEVIN KWAN - Nanta Adhitya, Galant; Wulandari, Novi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
The presence of literary works translated from foreign languages in Indonesia enriches the literary readership in region (Adi, 2016). In addition to gaining a wider readership, the understanding of the literary text will improve. Readers who may not fully understand the version in the original language have the opportunity to digest the story thoroughly. The comprehensive understanding becomes more important when dealing with foreign literature talking about Indonesia, such as Kevin Kwan's Crazy Rich Asians trilogy. The trilogy was translated into Bahasa as Kaya Tujuh Turunan (2016), Kekasih Kaya Raya (2017), and Masalah Orang Kaya (2018). This article examines how Indonesia is represented in the trilogy what factors influence the construction. The three novels were analyzed using the representation theory proposed by Stuart Hall with the descriptive-qualitative method. There are two representations of Indonesia, as a nation and as a state. Indonesian is represented of as a nation Chinese-Indonesians with their newly acquired wealth who are obsessed with having white skin and foreign husbands, on the one hand, non-Chinese Indonesians who work as manual due to lack of education on the other hand. Meanwhile, Indonesia as a state is represented as a developing rural country with rich and beautiful natural resources, yet are exploited by other countries and stolen by few government officials, resulting in weak economic and military situation.